Investigation of on-line optical particle characterization in reaction and cooling crystallization systems. Current state of the art - Abbas, Ali; Nobbs, Denis; Romagnoli, Jose A (Measurement science & technology, 2002)
Paper presented at the 6th International Congress on Optical Particle Characterization, Brighton, Apr 2001. Reviews particle size measurement applied to crystallization, with an overview of 2 available online techniques. 3 case studies were used: a suspension of aluminium oxide; reaction crystallization of nickel hydroxide; and cooling crystallization of ammonium sulphate. The aluminium oxide suspensions were used to appraise the accuracy of 2 online particle analysers: the Lasentec focused beam reflectance measurement (FBRM) based on back scattered laser light; and the Formulaction Turbiscan based on near-infrared light scatter. Results obtained were checked against the Malvern MasterSizer-S (based on the principle of laser ensemble light scattering) and a comparison was made between the analysers on the basis of mean particle size. The aluminium oxide and ammonium sulphate systems' crystal sizes were adequately measured using the Malvern. However, in the case of nickel hydroxide, the necessity to greatly dilute the suspension disrupted the agglomerate and generated a size not representative of the dynamic process. To conclude the experimental work, the online analysers were connected to a 1 l crystallizer using both reactive and cooling crystallization systems. It is shown that it is possible to track the crystal size using the Turbiscan while the FBRM generates a size distribution of chord lengths and is a practicable method for online crystal size tracking. (Original abstract - amended)